TEMPORAL AND SPATIAL CHANGES IN CROP DIVERSITY AND ITS IMPACT WITH SPECIAL REFERENCE TO DISTRICT PRAYAGRAJ: जनपद प्रयागराज के विषेष संदर्भ में फसल विविधता में सामयिक एवं स्थानिक परिवर्तन तथा प्रभाव - Yadav, Monika (International Journal of Research -GRANTHAALAYAH, 2021)
Abstract (English)- Human beings have to face different types of risks and uncertainties in their daily activities. Agriculture sector is also not untouched by it. Agriculture is fraught with uncertainty like rain, flood, drought and risk of diseases, pests and market fluctuation etc. In such a situation, undoubtedly crop diversity is a useful concept, which is very helpful for better use of agricultural resources and mitigation of risks related to agricultural production and providing quick and regular benefits to the farmers. Crop diversification refers to growing multiple crops instead of just a single crop, but crop diversification requires the highest level of managerial investment by each farmer. It is required to tackle the difficulties related to the low surplus, operation and marketing of the produce of agricultural products. Effective policy and investment are needed to overcome these difficulties. In fact, crop diversification exists as an effective strategy for achieving multiple aims like food security, nutritional security, poverty alleviation, availability of new employment opportunities, sustainable use of land, agricultural development and environmental improvement. (Hindi)- मनुष्य को अपने दैनिक गतिविधियों में विभिन्न प्रकार के जोखिमों तथा अनिश्चितता का सामना करना पड़ता है। कृषि क्षेत्र भी इससे अछूता नहीं है किसान विभिन्न प्रकार की अनिश्चितता और जोखिमों को उठाते हुए कृषि कार्य करता है। वर्षा, बाढ़, सूखा आदि अनिश्चितता तथा रोग कीट तथा बाजार के उतार-चढ़ाव के जोखिमों से कृषि कार्य भरा हुआ है। ऐसे में निःसंदेह फसल विविधता उपयोगी संकल्पना है जो कृषि संसाधनों के बेहतर प्रयोग, तथा कृषि उत्पादों से संबंधित जोखिमों के न्यूनीकरण व किसानों को शीघ्र तथा नियमित लाभ प्रदान करने हेतु अत्यन्त सहायक है। फसल विविधता का अभिप्राय केवल एक ही फसल उगाने के स्थान पर कई फसलें उगाना है। किंतु फसल विविधता हेतु प्रत्येक किसान द्वारा प्रबंधकीय निवेश के उच्चतम स्तर की आवश्यकता होती है। कृषि उत्पादों के न्यून अधिशेष, संचालन तथा उत्पादन के विपणन से संबंधित कठिनाइयों को दूर करना वांछनीय है। इन कठिनाइयों को दूर करने हेतु प्रभावशाली नीति तथा निवेश की आवश्यकता है। वास्तव में फसल विविधता खाद्य सुरक्षा, पोषण सुरक्षा, गरीबी उन्मूलन, रोजगार के नए अवसर की उपलब्धता, भूमि का धारणीय प्रयोग, कृषि विकास तथा पर्यावरण सुधार के बहुउद्देश्य को प्राप्त करने के लिए एक प्रभावशाली रणनीति के रूप में विद्यमान है।